Drivers, Challenges, and Integration of Health 4.0 Societal Engagement: Evidence from Turkey - Ozum Egilmez; Gozde Koca (Istanbul Business Research (IBR), 2021)
In Turkey, a novel concept like Health 4.0 is a potential candidate seeking a solution. This paper aims to identify the scope of Health 4.0 via the perceptions gathered from appropriate vignettes with the focus of IoT stand and with the help of a qualitative approach in the first phase of the hybrid methodology. In the first phase of the study, the authors revealed the drivers and challenges of Health 4.0 by asking for the scope and awareness of Health 4.0. In the second phase of the study, the given replies to the vignettes (possible real-life scenarios) were classified into four main criteria that serve several challenges towards the adoption of Health 4.0, which were evaluated by the MACBETH (Measuring Attractiveness by a Category-Based Evaluation Technique) approach to identify main and sub-challenges towards the concept. In doing so, by analyzing in a multicriteria method, results would help to recheck and undermine the current debates around the Health 4.0 concept, helping to form many applicability levels in the future. The results revealed that security was the most important criteria followed by education, confidentiality, and the politics/manageability criteria as being the least important challenge.
Keywords: 650; Health 4.0; Sustainable Integration; Multi-Criteria Decision Making; Strategic Management; MACBETH